The Influence of Polymerization Type and Reinforcement Method on Flexural Strength of Acrylic Resin - Fonseca, Rodrigo Borges (ScientificWorldJournal, 2015)
The aim of this study was to evaluate the flexural strength of acrylic resin bars by varying the types of resin polymerization and reinforcement methods. Fourteen groups (N = 10) were created by the interaction of factors in study: type of resin (self-cured (SC) or heat-cured (HC)) and reinforcement method (industrialized glass fiber (Ind), unidirectional glass fiber (Uni), short glass fiber (Short), unidirectional and short glass fiber (Uni-Short), thermoplastic resin fiber (Tpl), and steel wire (SW)). Reinforced bars (25 × 2 × 2 mm) were tested in flexural strength (0.5 mm/min) and examined by scanning electron microscopy (SEM). Data (MPa) were submitted to factorial analysis, ANOVA, and Tukey and T-student tests (a = 5%) showing significant interaction (P = 0.008), for SC: Uni (241.71 ± 67.77)(a), Uni-Short (221.05 ± 71.97)(a), Ind (215.21 ± 46.59)(ab), SW (190.51 ± 31.49)(abc), Short (156.31 ± 28.76)(bcd), Tpl (132.51 ± 20.21)(cd), Control SC (101.47 ± 19.79)(d) and for HC: Ind (268.93 ± 105.65)(a), Uni (215.14 ± 67.60)(ab), Short (198.44 ± 95.27)(abc), Uni-Short (189.56 ± 92.27)(abc), Tpl (161.32 ± 62.51)(cd), SW (106.69 ± 28.70)(cd), and Control HC (93.39 ± 39.61)(d). SEM analysis showed better fiber-resin interaction for HC. Nonimpregnated fibers, irrespective of their length, tend to improve fracture strength of acrylics.